Moderate Islamic Education Through the Interpretation of Moderate Verses in the Tafsir Al-Ibriz by KH Bisri Mustofa - Muhammad Shohib (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This research aims to determine how moderate verses are interpreted according to KH Bisri Mustofa in Tafsir Al-Ibriz and moderate Islamic education according to KH Bisri Mustofa. This research method uses a library approach (Library Research) and a qualitative research type. This research involves researchers as key instruments in collecting, analyzing, and interpreting data from various library sources. Through a thematic interpretation approach, researchers found research results regarding the concepts emphasized by KH. Bisri Mustofa in his interpretation of moderate verses in the Koran. These concepts include the right to freedom in all aspects of life, including freedom of belief and rationalism in seeking the truth, as expressed in QS Al-Baqarah verse 256. Understanding of piety, social spirit regardless of racial, ethnic, or religious differences, and Polite behavior towards neighbors, even non-Muslims, as explained in QS Al-Mumlahanah verse 8, is the main basis in the concept of moderate Islamic education. Apart from that, research shows that the concept of moderation verses also teaches the values of getting to know each other, interacting, helping each other, and cross-religious cooperation to advance civilization, by QS Al-Hujurot verse 13. Having a moderate spirit and prohibiting extremism, as found in QS An-Nisa's verse 171, is the basis for forming a balanced Muslim character.